Arbuscular Mycorrhizal Fungi in Agriculture New Insights - Nogueira de Sousa, Rodrigo (IntechOpen, 2023)
A mycorrhizae is a symbiotic relationship between plants and fungi. Mycorrhizal fungi play important roles in plant root systems and soil biology and chemistry. Arbuscular Mycorrhizal Fungi in Agriculture - New Insights provides a comprehensive overview of arbuscular mycorrhizae. It is divided into three sections: "The Role of Mycorrhizae Fungi in Plant Growth", "The Effect of Mycorrhizae on Plant Nutrition and Protection" and "Mycorrhizae Biology and Development". Chapters provide a better understanding of these fungi, their application and management, and their effects on different types of plants.